Particle size, mill type, and added fat influence flow ability of ground corn - Groesbeck, C.N.; Lawrence, K.R.; Hastad, C.W.; Goodband, Robert D.; Tokach, Michael D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
We conducted three experiments to determine effect of particle size, mill type, and added fat on flow characteristics of ground corn. In Experiment 1, corn was ground with either a hammer mill or a roller mill to produce six samples with different particle sizes. The particle size for the corn ground with a roller mill ranged from 1,235 to 502 microns with standard deviation ranging from 1.83 to 2.03. Particle size for corn ground with a hammer mill ranged from 980 to 390 microns with standard deviation ranging from 2.56 to 2.12. All samples were dried 12 hours to equalize moisture content. Soy oil was then added at 0, 2, 4, 6, and 8% to each sample. Flow ability was determined by measuring angle of repose (the maximum angle measured in degrees at which a pile of grain retains its slope). A large angle of repose represents a steeper slope and poorer flow ability. There was a three-way interaction (P<0.05) between particle size, added fat, and mill type. Roller mill ground corn had better flow ability than hammer mill ground corn, and decreasing particle size while increasing added fat, increased the angle of repose. However as particle size decreased and added fat increased, the differences between hammer mill and roller mill ground grain decreased. Corn ground with a hammer mill without added fat had a similar angle of repose to corn ground with a roller mill that had 6% added fat. For both Experiments 2 and 3, batches of roller mill and hammer mill ground corn were sifted with a Ro-Tap tester through a stack of 13 screens. The material on top of each screen was then collected. Samples were dried 12 hours to equalize moisture content. Soy oil was added at 0, 4, and 8% to each sample. In Experiment 2, five roller mill samples were selected from different individual screens with mean particle size ranging from 1,415 to 343 microns and 5 hammer mill samples ranging from 1,382 to 333 microns. All samples were selected from the ground corn remaining on top of the individual screens. By selecting samples this way, both roller mill and hammer mill samples had similar particle size standard deviation (PSSD), ranging from 1.1 to 1.3. There was an interaction (P<0.05) between particle size, added fat, and mill type. Increasing fat and decreasing particle size increased the angle of repose. However, in fine ground hammer mill ground corn, the differences between amounts of added fat became less as particle size decreased, whereas in roller mill ground samples the differences were maintained. In roller mill ground grain samples, decreasing particle size had less negative impact on flow ability than in hammer mill ground grain. In Experiment 3, we used 4 roller mill and 4 hammer mill samples that were constructed from the previously collected grain. All samples were constructed to have a similar mean particle size (641 to 679 microns) with increasing PSSD (1.62 to 2.27). There was no interaction (P>0.10) between PSSD, added fat, and mill type. Increasing fat (P<0.04) and PSSD (P<0.001) decreased flow ability. These data suggest that the greater flow ability of roller mill ground corn compared to hammer mill ground corn appears to be a result of less particle size variation. However, with fine particle sizes other factors, such as particle shape, may also contribute to flow ability.
Keywords: Particle size; Added fat; Hammer mill; Roller mill; Swine